2012
DOI: 10.5505/agri.2012.38247
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound guided supraclavicular and infraclavicular approaches for brachial plexus blockade.

Abstract: SummaryObjectives: Ultrasound-guided supraclavicular and infraclavicular blocks are commonly used for upper extremity surgery. The primary aims of our study were to compare block success, block onset times and performance times; secondary aims were to compare the number of needle advancements, and incidence of adverse events of ultrasound-guided supraclavicular or infraclavicular blocks. Methods: 110 patients were randomized into two groups: supraclavicular (Group S) and infraclavicular (Group I). All the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
10
1
2
Order By: Relevance
“…Previously published data about performance time vary considerably between studies [110]. The visibility scores demonstrated that the radial nerve in the AX BP block was the neural structure most difficult to visualize.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously published data about performance time vary considerably between studies [110]. The visibility scores demonstrated that the radial nerve in the AX BP block was the neural structure most difficult to visualize.…”
Section: Discussionmentioning
confidence: 99%
“…The observation period for these contingent immediate and early adverse events spanned the time in the block preparation area, in the operating theatre, and in recovery. Previous studies have reported a significantly higher number of early adverse effects associated with the SC BP approach [1, 3, 10], which has been a pivotal argument for opting out the SC BP technique in many surgical centers. Several dose-finding studies have been conducted using less than 20 mL of LA, but only one has compared various techniques for BP blockade [5] and only two studies reported on physiological adverse effects [25, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US, sağladığı görsel rehberlik sayesinde pnömotoraks riski nedeni ile kör tekniklerle daha az uygulanan supraklavikular ve infraklavikular bloğun giderek daha yaygın kullanılmasına neden olmaktadır. [23,24] US'nin blok tercihlerinde neden olduğu bir başka değişiklik ise alt ekstremitede siyatik sinirin klasik gluteal bölgede-ki bloğundan, US ile görüntülemenin daha kolay/ net yapılabildiği subgluteal ya da popliteal bölgeye doğru yer değiştirmesidir. [25] Tüm bunların yanı sıra son 10 yılda özellikle US rehberliği sayesinde daha rehberlik sinir lokalizasyonunun yanı sıra, iğne yerinin, ilaç dağılımının ve önemli anatomik komşu-lukların da görüntülenebilmesine olanak sağlamış-tır.…”
Section: Discussionunclassified
“…Pnömotoraks riski nedeni ile kör tekniklerle daha az uygulanan supraklavikular ve infraklavikular bloklar USG'nin görsel rehberlik sağlamasın-dan dolayı daha yaygın uygulanmaya başlanmıştır (21,22) .…”
Section: çElik Ve Arkunclassified